Market Valuation Analysis of NVIDIA Stock - Tu, Xun (Transactions on Economics, Business and Management Research, 2024)
NVIDIA is a semi-conductor company that designs and sells graphics processors. In recent years, its shares have traded at a premium to peers. This essay aims to analyze the market valuation of NVIDIA stock from both quantitative and qualitative perspectives and make recommendations for the company's stock traders.